Ai margini della crisi di un genere. Le 'Lettere' di Chiara Matraini tra il "comporre" e lo "scrivere" (Quaderni di Gargnano, 2018)
The essay investigates Chiara Matraini’s letters, which appear at the beginning of two editions of her poetry (Rime) (1595; 1597). It focuses on the connection between the letters and the verse (rime) that follow and, more broadly, on the relationship between poetry and prose. The essay also examines how Matraini used her prose compositions both to demonstrate a level of literary accomplishment on a par with male writers and to shape her poetics.
Keywords: Chiara Matraini; Petrarchismo; Scrittrici del Cinquecento; Lettere; Rime; Lucca